Phantom thief Jeanne. Vol. 02 - Tanemura, Arina (Viz Media, 2014)
"Devastated by Chiaki's deceit, Maron decides to cut him out of her life and never to rely on anyone. After the announcement is issued that Phantom Thief Jeanne intends to steal another painting, Maron goes missing, leaving the painting for Phantom Thief Sinbad to take. Has Maron now turned her back on being Phantom Thief Jeanne too?" -- Back cover.